The Inheritance of Activism: Does Social Capital Shape Women's Lives?. Issue 2 (1st June 2020) - Baily, Supriya; Wang, Gloria; Scotto-Lavino, Elisabeth
Abstract: In the call for proposals for this special issue, activist networks were defined as virtual or in person communities devoted to social change. The impact for girls active in these networks has been shown to promote identity development and de-marginalization/empowerment/reclamation of political spaces where girls are marginalized, intergenerational collaboration among women, and community building among feminists. In this study, we seek to explore how women at different generational points reflect on and remember their engagement in social activism. Understanding how these generational shifts affect the impact of social capital on the lives of these women and the changes we might see as they mature into leaders will provide a platform to better understand the influence of belonging to such networks during girlhood.